Hydrogen Sulfi de Adsorption on Alumina/Graphene Oxide Composites at Ambient Temperature - Montree Hankoy; Mettaya Kitiwan; Chaiwat Phrompet; Chesta Ruttanapun; Rittichote Kaewpengkrow; Supawan Vichaphund; Duangduen Atong; Phacharaphon Tunthawiroon (Chiang Mai Journal of Science, 2022)
Hydrogen sulfi de (H2S) is one of the most common pollutants found in natural gas and industrial waste. Over the few decades, the removal of H2S has become a signifi cant problem. In the fi eld of a clean environment such as water purifi cation and toxic gas removal, graphene oxide (GO) has been found to have advantages. In this study, the infl uence of GO on alumina (Al2O3) as an adsorbent of H2S was examined. A series of Al2O3/GO (AGO) composites with varying graphene oxide addition (0.5–3.0 wt%) were prepared using the high-temperature sintering method. The X-ray diffraction patterns indicate the primary phase of Al2O3 with hexagonal crystal structure for all AGO composites. Raman spectrometry measurements confi rmed that the GO particles were incorporated in AGO composites. The TEM image indicated that GO nanosheets were embedded between Al2O3 grains. The effi ciency of AGO adsorbent at ambient temperature was investigated and compared with the pristine Al2O3 adsorbent. The AGO composites adsorbent demonstrated the H2S breakthrough capacity in the range of 0.07–0.43 mg/g, which is higher than that of pristine Al2O3 (0.06 mg/g). Furthermore, the highest H2S breakthrough capacity of 0.43 mg/g was obtained from AGO containing 3.0 wt% GO. This investigation demonstrates that the AGO adsorbent fabricated using a simple method has the potential to be used for H2S removal at ambient temperature.
Keywords: Industrial Gas Emission Control